Teaching Practice of Promoting Writing through Reading in High School English Based on the Output-Oriented Approach (POA): Taking the Teaching of Cultural Heritage in the Second Compulsory Course of the People’s Education Edition as an Example - Wang, Ting; Huang, Yan (Education Insights, 2026)
Based on the output-oriented approach (POA), this paper takes "Promoting Culture Through Digital Images" in Unit 1 Cultural Heritage of Compulsory High School English Textbook 2 of the People’s Education Edition as a primary illustrative example. This article systematically explores the pedagogical practice of promoting reading through writing in high school English classrooms based on the POA framework. The "output-facility-selective learning" hypothesis of POA provides a robust theoretical basis for this methodology, while the structured "facility-facility-evaluation" teaching process provides a clear, actionable operational path for effective classroom implementation. By integrating these elements, educators can design more engaging and productive lessons. Extensive teaching practice demonstrates that POA-guided reading-to-writing instruction can effectively stimulate students’ intrinsic writing motivation, significantly promote the cognitive internalization and practical transfer of complex language knowledge, and successfully achieve the deep, meaningful integration of reading input and writing output. Furthermore, this innovative instructional model addresses common challenges in traditional language teaching by emphasizing active student participation and continuous assessment. Ultimately, the application of the output-oriented approach provides a highly feasible and sustainable path for implementing the core literacy objectives of the high school English subject, fostering comprehensive linguistic competence and cultural awareness among students in contemporary educational settings.